A simulation study on using (252)Cf for the treatment of esophagus tumor in human phantom - Rasouli, Fatemeh S. (EJNMMI Phys, 2020)
Due to the sensitivity of this tissue, and the potential for metastasis of its cancer as well, finding accurate methods to be employed for the treatment of esophagus tumors is of especial interest for the researchers. The present study deals with a Monte Carlo simulation of (252)Cf neutron brachytherapy for treating these tumors using MCNPX (Version 2.6.0) code. The widely accepted AAPM TG-43 protocol has been used to benchmark the simulated source and to examine the accuracy of the modeling. The MIRD human phantom has been used for dose evaluation in the mentioned tumor and in the surrounding normal tissues as well. To decrease the dose delivered to the healthy tissue, using appropriate shields has been proposed. Through dosimetric calculations for several candidates, Pt-Ir 10% with a thickness of 1 cm has been selected as the optimized shield. The depth-dose results as well as the isodose curves corresponding to the presence of the shielded (252)Cf neutron source in the center of the simulated tumor offer this source as an appropriate candidate to be used for the treatment of the esophagus tumors and sparing normal tissues. For a suggested clinical condition of positioning the source inside the esophagus, the damage to the first depth in spine can be avoided by managing the treatment time.